2010
DOI: 10.1002/jmri.22085
|View full text |Cite
|
Sign up to set email alerts
|

MRI and S‐MRCP findings in patients with suspected chronic pancreatitis: Correlation with endoscopic pancreatic function testing (ePFT)

Abstract: Purpose: To review magnetic resonance imaging (MRI) and secretin stimulated magnetic resonance cholangiopancreatography (S-MRCP) findings of patients with suspected chronic pancreatitis and compare them with endoscopic pancreatic function testing (ePFT). Materials and Methods:MRI and S-MRCP findings of 36 patients with clinically suspected chronic pancreatitis were reviewed. Baseline ductal changes, duodenal filling grades, and pancreatic duct caliber change (PDC) on S-MRCP, mean values of pancreatic anteropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 21 publications
1
53
0
Order By: Relevance
“…Abnormal endoscopic pancreatic function testing (ePFT) results have been reported to correlate moderately with diminished arterial perfusion 25. Secretin magnetic retrograde cholangiopancreatography (s-MRCP) has also been used to evaluate both the exocrine function of the pancreas and pancreatic duct compliance, thus excluding potential early structural changes not seen on MRI and MRCP.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal endoscopic pancreatic function testing (ePFT) results have been reported to correlate moderately with diminished arterial perfusion 25. Secretin magnetic retrograde cholangiopancreatography (s-MRCP) has also been used to evaluate both the exocrine function of the pancreas and pancreatic duct compliance, thus excluding potential early structural changes not seen on MRI and MRCP.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of PEI by magnetic resonance imaging and endoscopic ultrasound is, as of now, limited to conservatively managed patients with chronic pancreatitis [51][52][53][54].…”
Section: Predictors For Pei Following Pancreatic Surgerymentioning
confidence: 99%
“…Currently, endoscopic pancreatic function testing (ePFT) is considered the most reliable test for exocrine pancreatic function, but it is invasive and time-consuming [12]. In recent years, it has been reported that the efficacy of S-MRCP is comparable to that of ePFT in the evaluation of CP [12,18], and the assessment of exocrine pancreatic function using S-MRCP is highly correlated with tubeless tests (that is, FE-1 and pancreolauryl) [1]. Demonstrating a correlation between S-MRCP findings and CP histopathology will further support the use of S-MRCP for judging the severity in this disease.…”
Section: Discussionmentioning
confidence: 99%